Studying survivors of near-lethal suicide attempts as a proxy for completed suicide in prisons - Rivlin, A; Fazel, S; Marzano, L; Hawton, K (2012)
Suicides in prisons are common. There is a pressing need to understand more about the causes and prevention of prisoner suicides. A particularly informative approach is through studying survivors of near-lethal suicide attempts. However, the extent to which this approach is a good proxy for completed suicide requires verification. In this article we aimed to assess (1) the extent to which male and female prisoners who made near-lethal suicide attempts in prison are similar to prisoners who die by suicide; (2) the suicidal intent of those making near-lethal suicide attempts; and (3) the applicability of the Suicide Intent Scale in prisons. Survivors of near-lethal suicide attempts and prisoners who died by suicide were compared on sociodemographic and criminological characteristics. The suicidal intent of prisoners engaging in near-lethal self-harm was assessed using Beck's Suicide Intent Scale. There were no significant differences when the sociodemographic and criminological profiles of prisoners who made near-lethal suicide attempts and those who died by suicide were compared, except that male prisoners who made near-lethal suicide attempts were somewhat younger. Most prisoners carrying out near-lethal acts had high suicidal intent. However, some questions in the Suicide Intent Scale were inappropriate for assessing intent in prisoners. Prisoners who survive near-lethal self-harm would appear to be a valid proxy for those who die by suicide in prison. The Suicide Intent Scale requires some modifications for use in prisons. © 2012 Elsevier Ireland Ltd.